2007
DOI: 10.4028/www.scientific.net/ssp.121-123.1241
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Surface Dissolution in Dense Hydroxyapatite

Abstract: In this study, it was demonstrated how second phases with small amount, which are hardly detected by XRD analysis, affect grain boundary dissolution and related mechanical properties of HA. All HA disks sintered at 1200 oC for 2 h in air with under moisture protection were phase pure and had Ca/P molar ratio of 1.67. Following certain period of exposure to the distilled water, the surface dissolution initiated at grain boundaries and particle loosening, subsequently resulting in decrease in mechanical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…XRD analysis in our previous study showed that the artificial HA was phase-pure without any trace of impurities, such as tricalcium phosphate (TCP) and calcium oxide. 44 HA sintered body exhibited sintered density of 98% above of the theoretical density corresponding to the nearly fully densified microstructure without residual pores. Therefore, the artificial HA was not supposed to be dissolved in liquid environment.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…XRD analysis in our previous study showed that the artificial HA was phase-pure without any trace of impurities, such as tricalcium phosphate (TCP) and calcium oxide. 44 HA sintered body exhibited sintered density of 98% above of the theoretical density corresponding to the nearly fully densified microstructure without residual pores. Therefore, the artificial HA was not supposed to be dissolved in liquid environment.…”
Section: Resultsmentioning
confidence: 96%
“…Preparation and source of the artificial HA were described previously. 44 Briefly, phase-pure HA powder was synthesized by a precipitation reaction between mixture of Ca(NO 3 ) 2 AE4H 2 O and H 3 PO 4 , and ammonium hydroxide solutions. HA ceramics were obtained by sintered at 1200°C for 2 h in air with under moisture protection.…”
Section: Preparation Of Ha From Teethmentioning
confidence: 99%
“…Figure 3 shows the microstructures of HA ceramics prepared from lab-produced powder with immersion period. The HA ceramics used in this work consist of monophase hydroxyapatite without any second phases [13]. The relative density of the HA sintered body was 98 % of the theoretical density, showing a nearly fully densified microstructure and smooth surface, as shown in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…In a recent study by the authors [13], evidence of D-tricalcium phosphate (D-TCP) present in the vicinity of grain boundaries was observed by transmission electron microscopy (TEM) accompanied by high-resolution electron microscopy (HREM). In actuality, the quantity D-TCP was exceedingly small and thus was difficult to detect using intensive XRD analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation